2022
DOI: 10.5551/jat.rv17062
|View full text |Cite
|
Sign up to set email alerts
|

The Future Role of High-Performance Computing in Cardiovascular Medicine and Science -Impact of Multi-Dimensional Data Analysis-

Abstract: Advances in High-performance computing (HPC) technology have reached the capacity to inform cardiovascular (CV) science in the realm of both inductive and constructive approaches. Clinical trials allow for the comparison of the effect of an intervention without the need to understand the mechanism. This is a typical example of an inductive approach. In the HPC field, training an artificial intelligence (AI) model, constructed by neural networks, to predict future CV events with the use of large scale multi-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…MD simulation is not a novel technic, 42 but has become an important tool for clarifying the biological functions of various proteins due to rapid progress in the calculation power of high-performance computers. [43][44][45] The establishment of coarse-grained force fields based on quantum mechanics into molecular mechanics such as the Chemistry at HARvard Macromolecular Mechanics (CHARMM) force field 19,46 helped to generate comprehensive results from MD calculations. 42 Due to theoretical limitations, the validity of the calculated results of MD simulation should be confirmed by other methodologies, such as biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…MD simulation is not a novel technic, 42 but has become an important tool for clarifying the biological functions of various proteins due to rapid progress in the calculation power of high-performance computers. [43][44][45] The establishment of coarse-grained force fields based on quantum mechanics into molecular mechanics such as the Chemistry at HARvard Macromolecular Mechanics (CHARMM) force field 19,46 helped to generate comprehensive results from MD calculations. 42 Due to theoretical limitations, the validity of the calculated results of MD simulation should be confirmed by other methodologies, such as biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of high-performance computer and deep learning (DL) technologies has enabled the construction of models that detect diseases, predict outcomes, and automate measurements using raw ECG voltage data. 8 , 9 Several DL models have shown the ability to perform tasks beyond that of expert ECG operators. 10 , 11 , 12 By leveraging the power of DL in detecting subtle ECG changes, we aimed to enhance the screening process for ASD by building an accurate and scalable model to identify patients who should undergo further diagnostic tests with echocardiograms.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning with neural networks has evolved as a powerful tool to build clinically useful tools from complex medical data. 1 Recent studies have shown that the technology is capable of detecting diseases and predicting prognosis beyond the ability of fully trained experts. 2 , 3 , 4 However, the neural network model usually comes with the cost of the black box nature: not being able to explain why they predict what they predict.…”
mentioning
confidence: 99%